Injectable magnesium-bisphosphonate MOF-based bone adhesive prevents excessive fibrosis for osteoporotic fracture repair - Tianhua Xiao; Zunlei Gong; Dongming Duan; Hui Yu; Song Liu; Yuhe Jiang; Xudan Xing; Zenghui Wu; Le Wang; Xuebin B. Yang; Giuseppe Tronci; Chengyun Ning; et al. (Nature Communications)
Abstract Current treatments for osteoporotic fractures primarily target bone-resorbing osteoclasts, but they often fail to address fibrosis—a buildup of fibrous tissue that disrupts bone healing. This fibrosis is frequently triggered by bisphosphonates, which, while effective in reducing bone loss, also activate fibroblasts and impair callus formation. Here we show that an injectable hydrogel bone adhesive composed of magnesium-alendronate metal-organic frameworks (Mg-ALN MOF) embedded in a gelatin/dialdehyde starch network can simultaneously suppress bone resorption and reduce fibrosis. The Mg-ALN MOF adhesive binds firmly to irregular bone surfaces and degrades under acidic osteoporotic conditions, gradually releasing Mg2+ ions. These ions competitively bind to sclerostin (SOST), thereby interrupting the SOST/TGF-β signaling pathway that promotes fibroblast activation and abnormal collagen deposition. This dual-action mechanism significantly enhances fracture healing, resulting in a 27.8% improvement in flexural strength. Our findings suggest a promising therapeutic strategy that combines mechanical support with targeted regulation of both bone resorption and pathological fibrosis.